Safeguarding Personal Data in Indonesian E-Commerce from a Constitutional Rights Perspective - Mariyam, Siti; Satria, Adhi Putra; Hariyanto, Hariyanto; Masum, Ahmad (Faculty of Law, Jambi University, 2025)
The increasingly massive digital transformation has driven significant growth in e-commerce transactions in Indonesia, but it has also increased risks to consumers' personal data security and privacy. This research analyzes personal data protection in e-commerce transactions through a constitutional rights perspective. The research method used is a normative juridical approach, with a statutory, case-based, and comparative approach. The results show that although the constitution provides a normative basis for privacy protection, its provisions are still general and require elaboration through sectoral and comprehensive regulations, such as the Personal Data Protection Law. However, its implementation still faces challenges, including weak compliance by electronic system administrators, a lack of digital literacy among the public, the absence of a truly independent supervisory authority, and increasing cyber threats. Meanwhile, in Singapore, the Personal Data Protection Act (PDPA) demonstrates that successful data governance depends on a strong regulatory framework, an independent supervisory body, and a culture of organizational accountability. Based on this comparison, the study recommends a more operational and proactive data protection strategy, including the establishment of a Centralized Data Breach Response Hub, the implementation of privacy by design and privacy by default, and the development of a national roadmap that integrates technological innovation, institutional reform, and cross-sector collaboration